Literasi Keuangan Syariah bagi Anak School Age (Studi Kasus Pada Siswa Kelas 2 SD Darul Hikam Bandung) - Senjiati, Ifa Hanifia; Anshori, Arif Rijal; Maulida, Ira Siti Rohmah; Wahyudin, Yadi (UPT Publikasi Ilmiah UNISBA, 2018)
Sharia financial literacy index in Indonesia by Financial Services Authority in 2016 is 8%. Consists of the youngest respondents aged 13-15 years. The index level of Islamic financial literacy at that age is 2.2%. It means that under 13 years of age in the elementary school category or school age has never been studied. Formulation and objectives of the study (1) to know the concept of Islamic financial literacy for school age children and (2) to analyze the level of syariah financial literacy in 2nd grade students of SD Darul Hikam Bandung. The method used is descriptive analysis method, with 43 samples as respondents. Techniques of research using interviews assisted with research instruments of list questions in the google form. The results showed that 1) financial literacy for school age has 20 indicators that are divided into 3 categories: money literacy, money management literacy, and syariah financial literacy. And 2) syariah financial literacy in 2nd grade students of SD Darul Hikam as much as 68,8% respondents have syariah financial literacy at level of sufficient literate.